Prevalence of parkinsonism and Parkinson disease in urban and rural populations from Latin America: A community based study - Jorge J Llibre-Guerra; Matthew Prina; Ana Luisa Sosa; Daisy Acosta; Ivonne Z. Jimenez-Velazquez; Mariella Guerra; Aquiles Salas; Juan C Llibre-Guerra; Adolfo Valvuerdi; Geeske Peeters; Ellen Ziegemeier; Isaac Acosta; et al. (Elsevier, 2022)
Summary: Background: Age and gender specific prevalence rates for parkinsonism and Parkinson's disease (PD) are important to guide research, clinical practice, and public health planning; however, prevalence estimates in Latin America (LatAm) are limited. We aimed to estimate the prevalence of parkinsonism and PD and examine related risk factors in a cohort of elderly individuals from Latin America (LatAm). Methods: Data from 11,613 adults (65+ years) who participated in a baseline assessment of the 10/66 study and lived in six LatAm countries were analyzed to estimate parkinsonism and PD prevalence. Crude and age-adjusted prevalence were determined by sex and country. Diagnosis of PD was established using the UK Parkinson's Disease Society Brain Bank's clinical criteria. Findings: In this cohort, the prevalence of parkinsonism was 8.0% (95% CI 7.6%-8.5%), and the prevalence of PD was 2.0% (95% CI 1.7%-2.3%). PD prevalence increased with age from 1.0 to 3.5 (65-69vs. 80 years or older, p < 0.001). Age-adjusted prevalence rates were lower for women than for men. No significant differences were found across countries, except for lower prevalence in urban areas of Peru. PD was positively associated with depression (adjusted prevalence ratio [aPR] 2.06, 95% CI 1.40-3.01, I2 = 56.0%), dementia (aPR 1.57, 95% CI 1.07- 2.32, I2 = 0.0%) and educational level (aPR 1.14, 95% CI 1.01- 1.29, I2 = 58.6%). Interpretation: The reported prevalence of PD in LatAm is similar to reports from high-income countries (HIC). A significant proportion of cases with PD did not have a previous diagnosis, nor did they seek any medical or neurological attention. These findings underscore the need to improve public health programs for populations currently undergoing rapid demographic aging and epidemiological transition. Funding: The funding source had no role in the design and conduct of the study; collection, management, analysis, and interpretation of the data; preparation, review, or approval of the manuscript; and decision to submit the manuscript for publication.